Existence and stability of fractional complex Liu system - Rabha W. Ibrahim (Songklanakarin Journal of Science and Technology (SJST), 2014)
In this work, we consider the stability and stabilization of complex fractional Liu system. We assume the fractional calculus in sense of the Caputo derivatives (real and complex). The method based on stability theory of fractional-order systems. Numerical solutions are imposed. Moreover, conditions of unique solution are established.